Identification of nitric oxide as an endogenous inhibitor of 26S proteasomes in vascular endothelial cells. - Hongtao Liu; Shujie Yu; Hua Zhang; Jian Xu (PLoS ONE)
The 26S proteasome plays a fundamental role in almost all eukaryotic cells, including vascular endothelial cells. However, it remains largely unknown how proteasome functionality is regulated in the vasculature. Endothelial nitric oxide (NO) synthase (eNOS)-derived NO is known to be essential to maintain endothelial homeostasis. The aim of the present study was to establish the connection between endothelial NO and 26S proteasome functionality in vascular endothelial cells. The 26S proteasome reporter protein levels, 26S proteasome activity, and the O-GlcNAcylation of Rpt2, a key subunit of the proteasome regulatory complex, were assayed in 26S proteasome reporter cells, human umbilical vein endothelial cells (HUVEC), and mouse aortic tissues isolated from 26S proteasome reporter and eNOS knockout mice. Like the other selective NO donors, NO derived from activated eNOS (by pharmacological and genetic approach) increased O-GlcNAc modification of Rpt2, reduced proteasome chymotrypsin-like activity, and caused 26S proteasome reporter protein accumulation. Conversely, inactivation of eNOS reversed all the effects. SiRNA knockdown of O-GlcNAc transferase (OGT), the key enzyme that catalyzes protein O-GlcNAcylation, abolished NO-induced effects. Consistently, adenoviral overexpression of O-GlcNAcase (OGA), the enzyme catalyzing the removal of the O-GlcNAc group, mimicked the effects of OGT knockdown. Finally, compared to eNOS wild type aortic tissues, 26S proteasome reporter mice lacking eNOS exhibited elevated 26S proteasome functionality in parallel with decreased Rpt2 O-GlcNAcylation, without changing the levels of Rpt2 protein. In conclusion, the eNOS-derived NO functions as a physiological suppressor of the 26S proteasome in vascular endothelial cells.